The Association Between Platelet Indices and Clinical Parameters in Recurrent Pregnancy Loss - Sümeyra Nergiz Avcıoğlu; Sündüz Özlem Altınkaya; Mert Küçük; Selda Demircan Sezer; Hasan Yüksel (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Etiology of recurrent pregnancy loss (RPL) is variable. Hypercoagulability is one of the treatable conditions causing RPL. Platelet (PLT) count, mean PLT volume (MPV), PLT distribution width (PDW) and plateletcrit (PCT) are platelet indices and may be markers for increased platelet aggregability. In the present study, we aimed to determine and compare PLT count, MPV, PDW and PCT between patients with RPL and healthy controls. STUDY DESIGN: A total number of 39 patients with RPL and 40 healthy controls were enrolled in the research. PLT count, MPV, PDW and PCT values were compared between the patients and the controls. RESULTS: There were no statisti¬cally significant differences in number of PLTs, MPV, PCT and PDW values between women with RPL and healthy women (p> 0.05). CONCLUSION: Thrombocyte indices have still an unsatisfactory value in RPL and it seems that they are not appropriate for routine clinical practice regarding RPL.